Voltammetric Determination of Iron in Powder Milk - Ahmad Razali, Ishak (PPSP, Universiti Sains Malaysia, 2007)
In this study, voltammetric method which is one of the electro analytical techniques is described. The research focused on adsorptive stripping voltammetry (AdSV) in the presence of catechol for confirmation of electro analytical properties of iron. The analysis was carried out after acid digestion procedure then measurement was made using phosphate buffer 7.0 as the supporting electrolyte. The electrodes used in this analysis were hanging mercury dropping electrode (HMDE) which act as the working electrode, a platinum electrode as auxiliary electrode and Agl AgKCI reference electrode respectively. Optimum voltammetric parameter for the analysis of the sample such as initial potential, final potential, deposition potential, deposition time and scan rate were determined prior to sample analysis using iron standard solution at 1 ppm. The result showed that the optimum voltammetric parameters for the determination of iron in powder milk were, initial potential, (Ei) ofO V, final potential (Er) of -0.7 V, deposition potential Eacc of -0.6 V, deposition time ofO s and scan rate of0.030 V/s were obtained. The pH 7.0 was found out to be the optimum voltammetric condition for the determination of iron in samples. 3 different samples of powder milk were analyzed. The result showed that, the sample A and B contained 0.5776 and 0.3075 ppm of trace iron respectively and no iron was detected in sample C